(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
A list of 68 species of Lepidoptera Tortricidae recorded on the Maltese Islands is reported. Phtheochroa ochralana Chrètien, 1915, Fulvoclysia nerminae Koçak, 1982, Cochylis moguntiana (Rossler, 1864), Aphelia unitana (Hiibner, [1796-99]), Lobesia indusiana (Zeller, 1847), Lobesia limoniana (Milliere, 1860), Eucosma fulvana (Stephens, 1834), Cydia fagiglandana (Zeller, 1841) and Cydia ulicetana (Haworth, [1811]) are new for the Maltese fauna. Phtheochroa ochralana is new for Europe.